2018
DOI: 10.1002/slct.201802404
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Ionic Liquid and Nanoparticles on Stabilizing Foam for Enhanced Oil Recovery

Abstract: One of the commonly used tool in enhance oil recovery (EOR) is nitrogen foam flooding. The sweeping efficiency is largely determined by the foam stability. Recently the study on using nanoparticle, alone or with other chemicals, to stabilize foam has emerged in several fields of foam application. In this study, we use a combination of physicochemical tools to analyze the synergetic effect of ionic liquid cetylpyridinium chloride (CPC) with nanoparticle in foam flooding of EOR. Two different nanoparticles (NPs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…NP were dispersed in Milli‐Q water with a surface tension of 72.5 ± 0.3 mN m −1 . Surface modifications were carried out on 20–30‐nm fumed silica NP (non‐functionalized, non‐porous, purity of 98 %) via three approaches: Dehydration of nanosilica surfaces through heat treatments (dehydrated nanosilica) Surface modification with the hydrophobic agent 3‐aminopropyl triethoxysilane (APTES) (functionalized nanosilica type A) Surface modification with both hydrophilic agents (poly(ethylene glycol) linked to 3‐glycidoxypropyltrimethoxysilane according to 24) and hydrophobic agents (trimethoxy(propyl)silane) (functionalized nanosilica type B) …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…NP were dispersed in Milli‐Q water with a surface tension of 72.5 ± 0.3 mN m −1 . Surface modifications were carried out on 20–30‐nm fumed silica NP (non‐functionalized, non‐porous, purity of 98 %) via three approaches: Dehydration of nanosilica surfaces through heat treatments (dehydrated nanosilica) Surface modification with the hydrophobic agent 3‐aminopropyl triethoxysilane (APTES) (functionalized nanosilica type A) Surface modification with both hydrophilic agents (poly(ethylene glycol) linked to 3‐glycidoxypropyltrimethoxysilane according to 24) and hydrophobic agents (trimethoxy(propyl)silane) (functionalized nanosilica type B) …”
Section: Methodsmentioning
confidence: 99%
“…Surface modification with both hydrophilic agents (poly(ethylene glycol) linked to 3‐glycidoxypropyltrimethoxysilane according to 24) and hydrophobic agents (trimethoxy(propyl)silane) (functionalized nanosilica type B)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the fact like this, the three-phase saturation distribution (TSD) is of great significance for a deeper understanding on the three-phase porous flow and better strategies for energy development and ecological conservation [1,[6][7][8][9]. Gas production and flooding, especially during coal mining [10][11][12], have a nonnegligible impact on brine storage in mining area [13][14][15][16]. In specific, the residual oil in micropores is conducive to plug the predominant pathways for a better brine storage [17,18], while the gas flooding probably displaces the brine and oil in micropores causing brine transfer, even leakage [4,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…It is not necessary for the nanoparticles to be amphiphilic. They can be hydrophilic as well; Jiang et al (2018) showed an example where the hydrophilic silica was more effective in foam flooding than relatively hydrophobic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%